Ultrastructural studies on the hypendyma of subcommissural organ of goat* - KUMAR, PAWAN; KUMAR, SURAJ (The Indian Journal of Animal Sciences, 2014)
The hypendyma of subcommissural organ was present below the ependyma just adjacent to posterior commissure. The hypendymal cells were classified into 2 types on the basis of nuclear morphology. Irregular shaped type-I cells nuclei possessed small aggregates of chromatin and nucleolus in the form of chromoplast. Type-II cells nuclei had nuclear clefts and uniform distribution. of fine chromatin matyrial. The cytoplasm of these cells contained different cell organelles and modified endoplasmic reticulum in the form ofNebenkerne. The glial component was constituted by micro and macroglial cells. A large pericapillary space and pores in capillary wall were characteristic features. Myelinated nerve fibres were present close to posterior commissure.